2017
DOI: 10.18203/2349-3933.ijam20171050
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile, bacterial profile and outcomes of acute bacterial meningitis in a tertiary care hospital– one year study

Abstract: Background: Bacterial meningitis is still one of the major causes of mortality and morbidity among all groups in developing countries. The mortality and prevalence of common pathogens has reduced in developing countries with implementation of successful vaccination against the pathogens. Laboratory surveillance of pathogens is crucial in formulating the empirical treatment guidelines and to identify the targets of immunization. The present study was undertaken to evaluate the clinical profile, bacterial pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…In this study 85 neonates (36.5%) had positive results for CSF culture, and about 1.5% of infants suspected for sepsis detected to have meningitis in our departments. In one study, positive result for CSF culture was reported in 36.88% (7). In another study, the prevalence of neonatal meningitis was 1% (22).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In this study 85 neonates (36.5%) had positive results for CSF culture, and about 1.5% of infants suspected for sepsis detected to have meningitis in our departments. In one study, positive result for CSF culture was reported in 36.88% (7). In another study, the prevalence of neonatal meningitis was 1% (22).…”
Section: Discussionmentioning
confidence: 94%
“…Knowledge about causative pathogens of meningitis helps for prompt diagnosis and treatment. In developing countries such as India, despite important advances in treatment, mortality rates of this disease is still 16-34% (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various reports across India have documented variations in MRSA prevalence which ranges from 17.6% to 80.4% depending on the geographical area. [20][21][22][23][24] Similarly, the survey identified 34% of the delegates who observed 10-20% of MRSA prevalence; while, another 30% delegates identified 20%-40% of MRSA in their respective ICU settings. This variation in prevalence rates could be attributed to the different ICU settings, patient profiles and local antibiotic regimen that could impact the overall prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…415 A recent Indian study including 266 culture positive ABM patients (including 142 CAM patients) found that gram positive pathogens exhibited maximum sensitivity to vancomycin and linezolid whereas most gram-negative pathogens were sensitive to carbapenems. 416 Seven days antibiotic therapy has been recommended for N. meningitidis and H. influenzae , 10–14 days for S. pneumoniae , 14–21 days for S. agalactiae , 21 days for aerobic GNB and 21 days or more for L. monocytogenes . 417…”
Section: Biliary Sepsismentioning
confidence: 99%